High Rate of Cytomegalovirus Detection in Cholestatic Preterm Infants - Jonas Teng (Frontiers Media S.A., 2021)
Objectives: To evaluate the prevalence of cytomegalovirus (CMV) infection in preterm infants with cholestasis.Study design: Preterm infants (<37 weeks gestational age) with cholestasis were tested for CMV DNA using Taqman PCR in blood cells from sedimented whole blood, plasma, and urine. Infants were regarded as positive for CMV if any sample was tested positive. Their mothers were tested for CMV serostatus simultaneously. A control group of non-cholestatic preterm infants, and their mothers, were tested at a similar age.Results: A total of 69 preterm infants with a median gestational age of 26 weeks and 5 days were included, 45 cholestatic and 24 non-cholestatic. Of the cholestatic infants, 31/45 (69%) were CMV positive vs. 3/24 (13%) of the non-cholestatic infants (p < 0.001). Cholestatic infants were equally preterm as the non-cholestatic ones, but were more severely ill. After adjusting for the risk factors necrotizing enterocolitis, prolonged parenteral nutrition, and gestational age, being CMV positive remained significantly associated with cholestasis in a multivariable logistic regression model. Characteristics of CMV-positive and -negative cholestatic infants showed differences only for necrotizing enterocolitis, occurring in 55% (17/31) of CMV positive vs. 21% (3/14) of CMV negative (p = 0.054), and mortality. Eight cholestatic CMV-positive infants died (26%) vs. none of the CMV-negative infants (p = 0.044).Conclusions: CMV DNA was detected in two out of three cholestatic preterm infants, by far more often than in the non-cholestatic control group. Cholestasis with simultaneous detection of CMV DNA may be associated with increased mortality.